Affordable Rental Housing: Making It Part of Europe’s Recovery - Elfayoumi, Khalid (Washington, D.C International Monetary Fund (IMF), 2021)
Many European economies have faced pressure from rental housing affordability that has widened social and economic divergence. While significant country and regional differences exist, this departmental paper finds that in many advanced European economies a large and rising share of low-income renters, the young, and those living in cities is overburdened. In several locations, middle-income groups also increasingly face rental affordability issues. (IMF page)
Abstract -- 1. Introduction and Main Findings -- 2. Key Characteristics of Rental Markets in Europe -- 3. Rental Housing Affordability: Key Facts -- 4. Main Factors Behind Declining Rental Affordability -- 5. Policies in Support of Affordable Rental Housing -- 6. Conclusions -- References
Includes bibliographical references (pages 77-88)
Keywords: Housing; HOUSING; RENTAL HOUSING; PRICES; INCOME DISTRIBUTION; EUROPE